A brief history of PINS - Hayes, Grahame (PINS-Psychology in Society, 2023)
The early 1980s was a vibrant and tumultuous time in South Africa as increasing challenges to the apartheid government were being mounted from all angles of the society. The state and its security forces were cracking down on anti-apartheid activists through large-scale detentions, and in turn individuals and organisations were responding with a combination of defiance and organized resistance in the formation of communitybased organisations. The highpoint of this organizational development was the formation of the UDF (United Democratic Front) in 1983 (20 August 1983 in the Western Cape), and COSATU (Congress of South African Trade Unions) in 1985 (1 December 1985 in Durban).